Feeding or starvation: which condition makes the red palm weevil, Rhynchophorus ferrugineus Olivier, more susceptible to insecticides? - Abdel-Baky, Nagdy F.; Alhewairini, Saleh S.; Alsalhee, Saleem A.; Alanazi, Turki S. M.; Alharbi, Raid R. (Frontiers in Insect Science, 2026)
IntroductionOver the last four decades, the red palm weevil (RPW), Rhynchophorus ferrugineus, has emerged as one of the most destructive pests of date and ornamental palms worldwide, causing major economic losses, with insecticide susceptibility strongly influenced by nutritional status.MethodsThis study assessed how feeding versus starvation affects the sensitivity of RPW larvae and adults to ten commonly used insecticides at three dose levels (½×, 1×, and 2× of the recommended rate). Mortality rates were recorded and compared between fed and unfed insects.ResultsStarvation significantly increased mortality, particularly in larvae, which were consistently more vulnerable than adults. Voliam Flexi achieved complete mortality under both conditions, whereas Coragen, Cyprone, and Indocarb caused full larval mortality only under starvation at the highest dose. In adults, 100% mortality with Medprid, Sivanto, Fiprol, and Deciban occurred only in starved insects. Feeding reduced insecticide toxicity, likely via enhanced detoxification or dilution of toxins through ingested sap, as indicated by lower LC₅₀ values in unfed insects for Sivanto, Coragen, Fedothrin, and Lamdoc.Discussion/ConclusionThese findings highlight feeding status as a critical determinant of insecticide efficacy. Pre-treatment starvation or natural food scarcity can enhance chemical performance, reduce insecticide use, and improve integrated pest management (IPM) strategies. The study also emphasizes the need for further research to elucidate the physiological mechanisms linking nutrition, detoxification, and insecticide susceptibility in RPW.” and confirmed as accurate.